2004
DOI: 10.1007/s00441-004-0992-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a neurofilament-like protein in the protocerebral tract of the crab Ucides cordatus

Abstract: Neurofilaments (NFs) have not been observed in crustaceans using conventional electron microscopy, and intermediate filaments have never been described in crustaceans and other arthropods by immunocytochemistry. Since polypeptides, labeled by the NN18-clone antibody, were revealed on microtubule side-arms of crayfish, we have tested, in this study, whether proteins similar to mammalian NFs are present in the protocerebral tract (PCT) of the crab Ucides cordatus. We used immunohistochemistry for light microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…However, as reported previously (Corrêa et al, 2004), we found NF proteins in regions corresponding to the MT side-arms in the crustacean protocerebral tract (PCT).…”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations
“…However, as reported previously (Corrêa et al, 2004), we found NF proteins in regions corresponding to the MT side-arms in the crustacean protocerebral tract (PCT).…”
Section: Introductionsupporting
confidence: 87%
“…Other numbers of protofilaments are possible: for example, certain MTs in the neurons of nematode worms contain 11 or 15 protofilaments (Karabinos et al, 2001). In crustaceans, there is at least one remarkable difference in the structure of MTs compared to vertebrates: the side-arms departing from the vertebrate MTs are constituted mainly by tau and MT-associated proteins (MAPs) (Hirokawa, 1986); whereas in crustaceans, besides MAP 2 (Bloom et al, 1984(Bloom et al, , 1985Matus et al, 1981), NF proteins also constitute the MT side-arms (Corrêa et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One series of sections was immediately dewaxed, hydrated, and stained with Mallory trichromic, hematoxylin and eosin or 5% toluidine blue for routine histological analyses. Series of sections destined for the immunohistochemical reactions were also dewaxed, hydrated, and then washed in PBS with 0.3% Triton X-100, incubated with 5% normal goat serum, and afterwards with the primary antibody overnight at 4 ° C. The primary antibodies used were: rabbit anti-serotonin diluted at 1: 100 (Sigma), based on Harzsch and Waloszek [2000], who used this label in order to enhance the visualization of functional neurites in decapod crustaceans, showing active neural routes; mouse anti-neurofilament medium (N-160), to reveal axon bundles [Corrêa et al, 2004] and rabbit anti-neurofilament high (N-200; Sigma), diluted at 1: 100; rabbit anti-neuronal nitric oxide synthase (NOS; Sigma) diluted 1: 100, for revealing projection neurons [Benton et al, 2007]; and rabbit anti-synapsin (synorf 1; Hybridoma bank), diluted at 1: 50, because it labels synaptic contacts; therefore the distribution this marker reveals directly relates to the synaptic and probably to the functional organization [Vilpoux et al, 2006;Harzsch and Mül-ler, 2007].…”
Section: Methodsmentioning
confidence: 99%
“…NN18, also called NF-160 or NF-M, reacts with the medium molecular weight (160 kDa) neurofilament subunit and labels exclusively neurofilaments in vertebrates as well as crab [30][33]. In the ascidian, it was found that NN18 recognizes a 58 kDa protein and strongly labels myoplasm in eggs from numerous species [13], [34]–[37].…”
Section: Introductionmentioning
confidence: 99%